Weighted composition operators between Fock spaces ℱ∞(ℂ) and ℱᵖ(ℂ) - Khoi, Le Hai (2021)
In this paper, we establish necessary and sufficient conditions for boundedness and compactness of weighted composition operators acting between Fock spaces ℱ∞(ℂ) and ℱᵖ(ℂ). We also give complete descriptions of path connected components for the space of composition operators and the space of nonzero weighted composition operators in this context.